3D mesoscopic architecture of a heterogeneous cellular network in the cementum–periodontal ligament–alveolar bone complex. (29th November 2021) - Hirashima, Shingo; Ohta, Keisuke; Togo, Akinobu; Nakamura, Kei-ichiro
Abstract: Cell-to-cell communication orchestrates various cell and tissue functions. This communication enables cells to form cellular networks with each other through direct contact via intercellular junctions. Because these cellular networks are closely related to tissue and organ functions, elucidating the morphological characteristics of cellular networks could lead to the development of novel therapeutic approaches. The tooth, periodontal ligament (PDL) and alveolar bone form a complex via collagen fibres. Teeth depend on the co-ordinated activity of this complex to maintain their function, with cellular networks in each of its three components. Imaging methods for three-dimensional (3D) mesoscopic architectural analysis include focused ion beam/scanning electron microscopy (FIB/SEM), which is characterized by its ability to select observation points and acquire data from complex tissue after extensive block-face imaging, without the need to prepare numerous ultrathin sections. Previously, we employed FIB/SEM to analyse the 3D mesoscopic architecture of hard tissue including the PDL, which exists between the bone and tooth root. The imaging results showed that the cementum, PDL and alveolar bone networks are in contact and form a heterogeneous cellular network. This cellular network may orchestrate mechanical loading–induced remodelling of the cementum–PDL–alveolar bone complex as the remodelling of each complex component is coordinated, as exemplified by tooth movement due to orthodontic treatment and tooth dislocation due to occlusal loss. In this review, we summarize and discuss the 3D mesoscopic architecture of cellular networks in the cementum, PDL and alveolar bone as observed in our recent mesoscopic and morphological studies.